Who has anaphylaxis in Brazil? Validation of a questionnaire for population studies - Gagete, Elaine; Delazari Dos Santos, Lucilene [UNESP]; Gomes De Pontes, Leticia [UNESP]; Morato Castro, Fábio (Elsevier, 2017)
Background: The incidence of anaphylaxis is increasing in several parts of the world; thus, determining the prevalence of the disease in a given region is important to understand the factors involved and to promote measures to avoid this type of allergic reaction. Aiming this objective, we validated an instrument for a population-basedstudy that assesses the prevalence of anaphylaxis in the Brazilian population. Methods: A questionnaire was generated in two variants - one for subjects seven years old or above (Group A) and another for children who were up to six years, 11 months and 29 days (Group B). The instrument was administered to patients with and without anaphylaxis. By allocating points, a score was calculated to differentiate subjects with and without the disease. After validation, the questionnaire was applied in the city of Botucatu (São Paulo state, Brazil), by randomly selecting houses and inviting residents to answer the questionnaire. Results: The questionnaire was reliable for identifying subjects with and without anaphylaxis in both groups, with a specificity and sensitivity above 90%. The prevalence of anaphylaxis in the pilot survey was 6.2% in Group A, however the evaluation was compromised in Group B by the low number of children below seven years of age due to random sampling of residences. Discussion: The prevalence of anaphylaxis in our pilot test (6.2%) was similar to major epidemiological surveys from several parts of the world, showing that anaphylaxis is not a rare disease. The instrument of the present work was suitable for this epidemiological survey and might be a good option for studying anaphylaxis in other populations. Conclusion: This instrument might be of particular value in places where researchers cannot access medical records to conduct similar epidemiological studies.
Keywords: Anaphylaxis; Epidemiology; Surveys and questionnaires